A copper(II) coordination polymer of formate-bridged dimers: an alternating S = ½ antiferromagnetic chain. Issue 3 (16th February 2023) - Addison, Anthony W.; Butcher, Raymond J.; Turnbull, Mark M.
Abstract: Reaction of 1, 3-propanediamine with copper(II) perchlorate hexahydrate in basic solution in the presence of trimethyl orthoformate and o -iodophenol serendipitously formed sodium [triformato-diperchlorato-di-1, 3-propanediaminodicopper(II)], Na[Cu2 (HCO2 )3 (1, 3-pn)2 ](ClO4 )2 (1 ). Single-crystal X-ray diffraction measurements show the compound to be a coordination polymer with the Cu(II) ions alternately bridged in μ1, 1 - and μ1, 3 -fashion by the formate ions. The sodium ions are coordinated to both formate ions and perchlorate ions in the lattice. Magnetic measurements were made over the range 1.8-310 K and show the presence of a singlet ground state at low temperature, the µ1, 1 -bridged copper ions being strongly antiferromagnetically coupled. The data were modeled equally well, within experimental error, by the alternating chain model and the dimer model with a Curie-Weiss correction for weak inter-dimer interactions, yielding C = 0.432(2) emu-K/mol-Oe, J /kB = −94.3(9) K and J ' = −2.4(1.5) K ( H =   − J ∑ S 1 · S 2 ). Abstract : UF0001